CPR decision-making conversations in the UK: an integrative review. Issue 1 (14th August 2018) - Hall, Charlie C; Lugton, Jean; Spiller, Juliet Anne; Carduff, Emma
Abstract : Objectives: Do Not Attempt Cardio-Pulmonary Resuscitation (DNACPR) discussions with patients and their caregivers have been subjected to intense ethical and legal debate in recent years. Legal cases and national guidelines have tried to clarify the best approach to DNACPR discussions; however, there is little evidence of how best to approach them from the patient, family or caregiver perspective. This paper describes published accounts of patient, family and caregiver experiences of discussions about advance cardiopulmonary resuscitation (CPR) decision making. Methods: An integrative review of the UK literature between 2000 and 2016 including qualitative and quantitative studies was conducted. Worldwide, 773 abstracts were identified, and 20 papers from the UK were included in the final analysis. Results: Patient, family and caregivers prefer discussions to be initiated by someone trusted, and wishes for family involvement vary depending on the context. Timing of discussions should be individualised, though discussions earlier in the illness are often preferable. Discussions held in the acute setting are suboptimal. CPR decisions should be part of a wider discussion about future care and adequate communication skills training is important. Conclusions: The findings of this review are at odds with the current statutory framework and potentially challenging for medical professionals who are working in a stretched health service, with pressure to discuss DNACPR decisions at the earliest opportunity. With increasing focus on person-centred care and realistic medicine, patient narratives must be considered by doctors and policy makers alike, to minimise harm.